THE PROPHETIC NATURE OF ALICJA LENCZEWSKA’S WRITINGS – TESTIMONIES” AND “WORDS OF INSTRUCTION” - Rachwalik, Walter (Studia Teologiczne Białystok Drohiczyn Łomża, 2024)
The Church, being faithful to God's Revelation, constantly proclaims the truth about the existence of fallen angels and deceived condemned human beings. It also warns against their sophisticated activities, with which they want to possess future generations and lead many to reject God. This theme is reflected in the supernatural instructions supposedly given by Jesus Christ to a resident of Szczecin, a Polish mystic, Alicja Lenczewska (1934-2012), exposing with remarkable accuracy their infernal perversity and indicating ways to defend against it.